Stages of Development of the Digital Economy - X. R. Bobobekova; M. X. Nurullayeva (International Journal on Human-Computing Studies, 2022)
Interest in the digital economy has grown significantly due to significant changes in society and the economy. Modern technologies and platforms have helped businesses and individuals reduce costs by minimizing personal interactions with customers, partners, and government organizations, as well as making communication faster and easier. The result is a digital or electronic economy based on network resources.